Lexical-semantic differention military vocabulary in Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article deals with the investigation peculiarities of military vocabulary in the Ukrainian language on the example of the names of the weapon. The regimentation names of weapon allows us to set the position of each lexeme in a coherent structure, to identify a set of semantic-paradigmatic connections and relationships between words in a lexical-semantic group and outside, as well as follow logical and linguistic consistency military vocabulary.
Keywords: extra-lingual factor; intra-lingual factor; military vocabulary; lexical-semantic group; paradigmatic relations